PENERAPAN METODE DRILL DALAM MENINGKATKAN KETERAMPILAN MENULIS PERMULAAN PESERTA DIDIK KELAS 1 SD NEGERI 111 PIDOLI DOLOK - Ariston Tanjung; Irma Suryani Siregar; Ali Yuseon (EDU RESEARCH, 2025)
This researcThis research aims to improve initial writing skills through the Drill method in class I of SD Negeri 111 Pidoli Dolok. This research is a classroom action research (PTK) that was conducted. in two cycles. This cycle consists of four stages, namely, planning, implementation, observation and reflection. The subjects of this research consisted of 15 students, 5 male students and 10 female students in class I of SD Negeri 111 Pidoli Dolok 2023/2024. Data collection tools in research. used observation and test sheets and for data analysis in this study used quantitative descriptives. The research results show that the learning process through the Drill method can improve students' initial writing skills by fulfilling the KKM. The improvement in initial writing skills can be seen from each cycle, in the pre-cycle the average score was 67, with learning completeness of 5 students (33.33%) after the researcher used the Drill method in cycle I, student achievement was still 60%, after repetition by continuing to stage II of cycle student achievement is said to be. increased with an average achievement of 85 with completeness. students is 100%. From these data it can be concluded that students' initial writing skills improved after researchers used the Driil method.